Effect of Cd treatment on phytochelatin synthesis in maize - Szalai, Gabriella (Acta Biologica Szegediensis, 2002)
Phytochelatins are Cys-rich peptides enzymatically synthesized by γ-Glu-Cys dipeptidyl transpeptidase, generally known as phytochelatin synthase. In the present work the enzymes of phytochelatin synthesis and cadmium (Cd) accumulation were investigated during Cd stress. Young maize plants were treated with 0.1 mM Cd for 48 hours. Roots and leaves were used for the experiments. The Cd was accumulated mainly in young leaves during the treatment but there was also accumulation in older leaves. In the roots the amount of Cd increased continuously. The Cd concentration was much higher in the roots than in the leaves. There were no changes in the photosynthetic parameters. The γ-glutamylcysteine synthetase (γ-ECS) activity did not change in the first six hours but there was a great increase in activity after one day. The activity of glutathione synthetase did not change in the leaves but increased to a slight extent in the roots after one hour. The phytochelatin synthase activity did not change after one day, but decreased on the 2nd day in the roots. An increase in the activity could be seen in the leaves during the 1st day, after which it remained constant.